Biomass of Scots pine-silver birch tree stand 25 years after afforestation of former agricultural land - Deptuła, Miłosz; Nienartowicz, Andrzej; Iwicka, Marta; Filbrandt-Czaja, Anna (Ecological Questions, 2017)
: In 2O15, the structure of a forest stand growing on former agricultural land in subunit 277n of the Przymuszewo Forest Division (Regional Directorate of State Forests RDSF in Toruń) was described. The study area was afforested in 199O - mostly with Scots pine (Pinus sylvestris L.), silver birch (Betula pendula Roth) and several seedlings of the European beech – after many years of agricultural cultivation of grain and potato crops. Characteristics of the forest stand comprised the following parameters: species composition and species diversity, density of individual components, the average tree diameter at breast height (DBH), and the height and aboveground biomass of trees divided into individual species. The species structure, dendrometric characteristics and spatial dis- tribution of trees studied in 2015 were compared with the situation assessed in 2000. Based on DBH and height values, as well as the use of dendrometric tables and basic wood density for tree species, the above- ground biomass and total biomass of trees with a minimum diameter of 7 cm were calculated. The aboveground and total biomass for trees with DBH less than 7 cm was calculated on the basis of density and weight of trees according to the classification into species and height classes. The aboveground and total biomass of the whole tree stand, including spontaneous non-native and invasive Padus serotina Ehrh., was compared with the standing biomass of agricultural areas in the Tuchola Forest region as well as with other Scots pine-silver birch plantations on former agricultural lands described in ecological literature. The paper presents also the differences in assessments of aboveground pine biomass at the study site obtained when using conver- sion factors established during direct measurements carried out in forests of the Przymuszewo Forest Division and conversion factors applied during inventories conducted in Poland according to the IPCC recommendations for international reporting submitted to the United Nations Economic Commission for Europe, FAO and UNFCCC